Does Fetal Size Affect Umbilical Artery Pulsatility Index in Pregnancies Complicated by Gestational Diabetes? - Libera Troìa; Alessandro Libretti; Stefania Ferrari; Anna Dotta; Sonia Giacomini; Erika Mainolfi; Federica Spissu; Alessia Tivano; Daniela Surico; Valentino Remorgida (Diabetology)
Objectives: Excessive fetal growth is the most common fetal complication associated with gestational diabetes (GDM), resulting in adverse short- and long-term outcomes. Our main objective was to evaluate the influence of excessive fetal growth on Doppler ultrasonographic measurements of the Umbilical Artery (UA) among women with GDM during the third trimester of pregnancy. Methods: A retrospective study among 472 women with GDM was conducted. UA-PI was measured by Doppler ultrasonography three different times during the third trimester of pregnancy at 28, 32, and 36 weeks. Pregnancies were grouped according to the fetal weight centile or birthweight in two groups: large for gestational age (LGA) group (>90th percentile or ≥4000 g at birth) and adequate for gestational age (AGA) group (<90th percentile or <4000 g at birth, not including the intrauterine growth restrictions). Results: In the LGA group (n = 57, 12.1%), women had higher BMI (p = 0.0001) and fasting blood glucose than the AGA group (97.08 ± 40.69 vs. 86.29 ± 39.58 mg/dL; p = 0.0550). They required insulin therapy more frequently to achieve glycemic control (63.2% vs. 34%, p = 0.0001). In LGA, UA-PI decreased progressively from 28 to 36 weeks (p = 0.0048). The most pronounced reduction occurred at 32 weeks (p = 0.0076). Conclusions: All fetuses from mothers with GDM had a significant and progressive decline in UA-PI during the third trimester of pregnancy. LGA fetuses showed lower UA-PI values compared with AGA fetuses. Since maternal hyperglycemia increases the risk of fetal overweight and GDM may represent a fetal vascular disorder, it therefore seems possible that in LGA fetuses, maternal hyperglycemia could influence the fetal vasculature.